Mechanical and X ray computed tomography characterisation of a WAAM 3D printed steel plate for structural engineering applications. (8th March 2021) - Al-Nabulsi, Z.; Mottram, J.T.; Gillie, M.; Kourra, N.; Williams, M.A.
Highlights: Construction industry can use WAAM 3D printed technology to optimise steel components. Mechanical properties are benchmarked against the material properties in Eurocode EN 1993–1-1. X-ray Computed Tomography is employed for quality insurance of the steel's integrity. Ductility of the WAAM steel limits this steel to static applications in building structures. Abstract: This paper reports an investigation to improve fundamental knowledge and understanding of 3D printing of steel in structural engineering. The process method examined is Wire and Arc Additive Manufacturing (WAAM) for the manufacturing of large-sized components. The mechanical properties of 3D printed Union K 40 - GMAW steel are determined and benchmarked against measured properties of EN 8 carbon medium steel. The results presented and discussed are from tensile coupon testing and X-ray Computed Tomography, with the latter inspecting an internal volume of the WAAM steel for: printing orientation; mapping porosity; interfacial variation between the printed layers. The key finding is that the mechanical properties of the WAAM steel satisfy the requirements for a structural steel grade for building structures as specified by Eurocode 3 (EN 1993–1-1).